Effects of abiotic stress and hormones on the expressions of five 13-CmLOXs and enzyme activity in oriental melon (Cucumis melo var. makuwa Makino) - Jie-ying LIU; Chong ZHANG; Qi SHAO; Yu-fan TANG; Song-xiao CAO; Xiao-ou GUO; Ya-zhong JIN; Hong-yan QI (Journal of Integrative Agriculture, 2016)
Abstract: Lipoxygenases (LOXs) are a group of non-heme, iron-containing enzymes and extensively involved in plant growth and development, ripening and senescence, stress responses, biosynthesis of regulatory molecules and defense reaction. In our previous study, 18 LOXs in melon genome were screened and identified, and five 13-LOX genes (CmLOX08, CmLOX10, CmLOX12, CmLOX13 and CmLOX18) were predicted to locate in chloroplast. Phylogenetic analysis result showed that the five genes have high homology with jasmonic acid (JA) biosynthesis-related LOXs from other plants. In addition, promoter analysis revealed that motifs of the five genes participate in gene expression regulated by hormones and stresses. Therefore, we analyzed the expressions of the five genes and LOX activity in leaves of four-leaf stage seedlings of oriental melon cultivar Yumeiren under abiotic stress: wounding, cold, high temperature and hydrogen peroxide (H2O2), and signal molecule treatments: methyl jasmonate (MeJA), abscisic acid (ABA) and salicylic acid (SA). Real time qPCR revealed that wounding and H2O2 induced the expressions of all the five genes. Only CmLOX08 was induced by cold while only CmLOX13 was suppressed by high temperature. ABA induced the expressions of CmLOX10 and CmLOX12 while inhibited CmLOX13 and CmLOX18. MeJA increased the 3 genes expressions except CmLOX08 and CmLOX13, whereas SA decreased the effect, apart from CmLOX12. All the abiotic stresses and signal molecules treatments increased the LOX activity in leaves of oriental melon. In summary, the results suggest that the five genes have diverse functions in abiotic stress and hormone responses, and might participate in defense response. The data generated in this study will be helpful in subcellular localization and transgenic experiment to understand their precise roles in plant defense response.